Small molecules released from islets of Langerhans determined by liquid chromatography – mass spectrometry. Issue 21 (14th May 2022) - Ogunkunle, Emmanuel O.; Donohue, Matthew J.; Steyer, Daniel J.; Adeoye, Damilola I.; Eaton, Wesley J.; Roper, Michael G.
Abstract : Islets of Langerhans are the endocrine tissue within the pancreas that secrete hormones for maintenance of blood glucose homeostasis. Abstract : Islets of Langerhans are the endocrine tissue within the pancreas that secrete hormones for maintenance of blood glucose homeostasis. A variety of small molecules including classical neurotransmitters are also released from islets. While the roles of most of these small molecules are unknown, some have been hypothesized to play a critical role in islet physiology. To better understand their role on islet function, a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed to separate and quantify 39 small molecules released from islets. Benzoyl chloride derivatization of analyte molecules was used to impart retention and facilitate electrospray ionization efficiency. Separation was achieved on a 2.1 × 150 mm column packed with 2.7 μm core–shell C18 particles. Calibration curves showed excellent linearity between the concentration and analyte response, with relative standard deviations of the analyte responses below 15% and limits of detection from 0.01–40 nM. The method was applied to examine small molecules released from murine and human islets of Langerhans after static incubation and perfusion with glucose. Results showed a decrease in secretion rates with increasing glucose concentration for most of the analytes. Secretion rates were found to be higher in human islets compared to their murine counterpart. This method will be useful in understanding the roles of small molecules in biological systems.